Analisis Pengaruh Kurs, Tingkat Suku Bunga, Dan Inflasi Terhadap Pergerakkan Indeks Harga Saham (Studi Kasus Pada Pt Bank Mandiri (Persero) Tbk Periode 2013-2015) - Ermawati, Winda; , Dra. Chuzaimah, M.M (2017)
The aim of this study to determine contribution variableexchange rates,interest rates, and inflation as partial and simultaneous concerning variable stock price.This study was conducted by taking the data from Bank Mandiri Tbk whichenrolled on the BEI as objects of studies. The data of this study uses data times series of exchange rate,interest rates, inflation and stock prices during2013- 2015 periods.The analytical method used in this study is multiple linear regression method which compares statistical hypothesis with the results.Theresults of regression may indicating the exchange rate, interest rates, and inflation significantly influence of stock price movement (α = 5%). The other analytical methods is t test and F test of result study, as well as the magnitude of the regression coefficient (R²).